Pengaruh Subjective Norm, Attitude Toward Behavior, Dan Self-Efficacy Terhadap Entrepreneurial Intention - Jordan Joyohadi Prawira; Nur Hidayah (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2021)
The purpose of this study is to determine the influence of subjective norm toward entrepreneurial intention, attitude toward behaviour toward entrepreneurial intention, self-efficacy toward entrepreneurial intention. Sample was collected with non-probability sampling and purposive sampling. The data were collected using online questionnaire by google form with a total of 105 respondent and were processed by using SmartPLS software. The results of this study indicate that subjective norm affects entrepreneurial intention, attitude toward behaviour affects entrepreneurial intention, self-efficacy doesn’t affect entrepreneurial intention. The results of this study is to know how to increase entrepreneurial intention among private college student at West Jakarta with the help of three independent variables.Tujuan dari penelitian ini untuk mengetahui pengaruh subjective norm pada entrepreneurial intention, pengaruh attitude toward behaviour pada entrepreneurial intention, pengaruh self-efficacy terhadap entrepreneurial intention. Teknik pemilihan sampel yang digunakan adalah non-probability sampling dan teknik pengambilan sampel adalah purposive sampling. Data diambil menggunakan kuisioner online melalui google form dengan jumlah total responden 105. Pengolahan data dilakukan dengan menggunakan software SmartPLS. Hasil penelitian ini yaitu subjective norm mempengaruhi entrepreneurial intention secara signifikan, attitude toward behaviour mempengaruhi entrepreneurial intention secara signifikan, self-efficacy tidak dapat mempengaruhi entrepreneurial intention. Hasil dari penelitian ini bertujuan untuk dapat mengetahui bagaimana cara meningkatkan intensi berwirausaha khususnya pada mahasiswa/i perguruan tinggi swasta di Jakarta Barat dengan penggunaan variabel independen yang ada.